Lean construction y su aporte al alcance de criterios de certificación de comportamiento ambiental de edificaciones - Aristizábal-Monsalve, Paula Andrea; Botero, Luis Fernando Botero; Vásquez-Hernández, Alejandro (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Lean Construction and Sustainable Construction are two philosophies implemented in the construction industry but are applied separately. Several studies have shown that their joint application can generate greater benefits in project sustainability, understanding that both share objectives such as decrease in waste and the addition of value to the client. This paper present how from these shared objectives, Lean tools can contribute to the qualification criteria of the building environmental performance certificates reaching up to 29% of the general qualification. The three tools with the highest contribution are Prefabricated construction, VSM and concurrent engineering, however, the contributions most mentioned by the authors correspond to Prefabricated construction, VSM, JIT and BIM.